Identification of dominant aerob bacteri in saliva of the patient with fixed ortodontic appliance - Donald R. Nahusona; Annisa Meydina (Journal of Dentomaxillofacial Science, 2018)
Objective: To understand kind of dominant aerob bacteria in patient’s saliva with orthodontic appliance.Material and Methods: This is a descriptive observational with cross sectional design. Sample was saliva as many as 16 patients with fixed orthodontic appliance. Saliva were taken with swab method using wood catton swab, then put into tube filled with stuart medium, then isolated to blood agar, after that put into incubator for 24 hours then carried out catalase test, H2O2 3%, and gram color test to obtain aerob bacteria.Results: Identified bacteria from patient’s saliva with fixed orthodontic appliance as many as 44 aerob bacteria positive gram, they are Streptococcus mitis, Streptococcus pneumoniae, Staphylococcus aureus, and Enterococcus faecalis. Negative gram aerob bacteria found 2 kinds of bacteria they are Pseudomonas aeruginosa, and Klebsiella pneumoniae.Conclusion: The most dominant bacteria is positive gram aerob bacteria that is Staphylococcus aureus.